PENGARUH INKLUSI DAN LITERASI KEUANGAN SYARIAH TERHADAP PENINGKATAN JUMLAH MAHASISWA PERBANKAN SYARIAH DI KOTA BINJAI - Raja Sakti Putra Harahap; Shantika Dewi (Universitas Islam Islam Sumatera Utara, 2020)
Knowledge of Islamic finance is growing as human needs are increasingly complex. This ability is related to personal intelligence to be effective for the realization of social welfare, which we cannot avoid, for example in determining future decisions related to short-term or long-term decisions indirectly. The purpose of this study was to determine the effect of inclusion and Islamic financial literacy on the increase in the number of Islamic banking students at STAI Al-Ishlahiyah Binjai. This research was conducted at STAI Al Ishlahiyah Binjai. The population in this study were 1373 students of Islamic banking at STAI Al-Ishlahiyah Binjai and a total sample of 93 respondents. The results obtained: 1) There is an effect of inclusion on the increase in the number of Islamic banking students (p = 0.000); 2) There is an effect of Islamic financial literacy on the increase in the number of Islamic banking students (p = 0.036); 3) There is an effect of inclusion and Islamic financial literacy on the increase in the number of Islamic banking students (p = 0,000). This proves that simultaneous inclusion, namely student financial access and Islamic financial literacy, namely understanding of Islamic finance affects the increasing number of Islamic banking students.